2010
DOI: 10.1117/1.3400721
|View full text |Cite
|
Sign up to set email alerts
|

Tissue perfusion measurements: multiple-exposure laser speckle analysis generates laser Doppler–like spectra

Abstract: Abstract. Variations in skin perfusion are easily detected by laser speckle contrast maps, but a robust interpretation of the information has been lacking. We show that multiple-exposure laser speckle methods produce the same spectral information as laser Doppler methods when applied to targets with embedded moving scatterers. This enables laser speckle measurements to be interpreted more quantitatively. We do this by using computer simulation of speckle data, and by experimental measurements on Brownian motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 25 publications
3
62
0
2
Order By: Relevance
“…For fully Doppler shifted speckle patterns, Thompson and Andrews 16 have shown that the Doppler power spectrum can be calculated using the second derivative of the squared contrast with respect to the exposure time T. Following their work, the second derivative of a partially Doppler shifted speckle pattern can be described by …”
Section: From Contrast To Doppler Power Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…For fully Doppler shifted speckle patterns, Thompson and Andrews 16 have shown that the Doppler power spectrum can be calculated using the second derivative of the squared contrast with respect to the exposure time T. Following their work, the second derivative of a partially Doppler shifted speckle pattern can be described by …”
Section: From Contrast To Doppler Power Spectrummentioning
confidence: 99%
“…14,15 Based on these relationships, Thompson and Andrews have demonstrated that the Doppler power spectrum can in fact be deduced from the speckle contrast if the contrast is resolved as a function of exposure time. 16 In most LASCA studies, however, only a single exposure time has been used. As a single exposure LASCA image contains information from all Doppler frequencies, it will produce perfusion estimates that to some extent are sensitive to both the speed and the amount of moving red blood cells.…”
mentioning
confidence: 99%
“…Thompson and Andrews 62 have suggested that this can effectively be done by using multiple exposures. They showed that between 10 and 15 exposures, with each successive exposure being double the previous one, are sufficient to produce data on a par with Doppler techniques.…”
Section: Velocity Distributionmentioning
confidence: 99%
“…The capability of LSR to assess blood coagulation status in real-time as demonstrated in this study will open new opportunities for assessing a patient's blood coagulation status at the point of care. The analysis of laser speckle patterns has been investigated for a number of biomedical applications such as the measurement of blood flow and tissue perfusion [33,34] and for skin surface roughness assessment [35]. LSR is distinct in that as it measures the viscoelastic properties of blood from time-resolved laser speckle intensity fluctuations to determine blood coagulation status in patients.…”
Section: Discussionmentioning
confidence: 99%